Cerebrospinal Fluid Features in Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Reverse Transcription Polymerase Chain Reaction (RT-PCR) Positive Patients. (8th August 2020) - Bellon, Mathilde; Schweblin, Cecilia; Lambeng, Nathalie; Cherpillod, Pascal; Vazquez, Jessica; Lalive, Patrice H; Schibler, Manuel; Deffert, Christine
Abstract: This study analyzed the cerebrospinal fluid features of 31 coronavirus disease 2019 (COVID-19) patients with neurological complications. We observed neither severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in the cerebrospinal fluid, nor intrathecal immunoglobulin G (IgG) synthesis but did observe signs of blood-brain barrier disruption. These results might serve as a basis for a better understanding of SARS-CoV-2 related neuropathogenesis.